Preparation and antibacterial activity of copper nanoparticle/halloysite nanotube nanocomposites via reverse atom transfer radical polymerization - Ding, X.; Wang, H.; Chen, W.; Liu, Jian; Zhang, Y. (Royal Society of Chemistry, 2014)
© the Partner Organisations 2014. Copper nanoparticle supported halloysite nanotubes with a 15 nm lumen and 30 nm external diameter via surface initiation reverse atom transfer radical polymerization were fabricated and showed good antibacterial activity against Escherichia coli (E. coli). This journal is